Schizophrenia of the Main Character Reflected in Jeff Baena’s Horse Girl Movie (2020) - siti Isrohayati; Ana Widiyanti (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
This study is aimed to analyze : (1) the schizophrenia of main character in Jeff Baena’s “Horse Girl” (2) the mental condition of Sarah as schizophrenic reflected in Jeff Baena’s “Horse Girl”. The study uses descriptive qualitative method to analyzed the film entitled “Horse Girl” directed by Jeff Baena’s as the objective of the research. The method of collecting data includes watching and reading, identifying, classifying, and selecting. The method of analyzing the data by displaying, explaining, and interpreting. The data analyzed by using Eugene Bleuler theory of schizophrenia and Sigmund Freud Psychoanalysis. The result of the study : (1) the schizophrenia of main character reflected in Jeff Baena’s Horse Girl such as primary symptoms of schizophrenia in the form of association and ambivalence and secondary symptoms in the form of hallucination and delusions; (2) the mental condition of Sarah as schizophrenic in form of feeling generalized anxiety disorder due to the delusion, stress and mood disorder and analyzed by using Sigmund Freud psychoanalysis.